Navigating Complexities: Morbidity and Outcomes in Women Undergoing Five or More Recurrent Cesarean Sections (Journal of Fatima Jinnah Medical University, 2022)
Background: Cesarean sections (CS) are increasingly common, especially in high-risk pregnancies. While generally safe, each additional CS increases the risk of complications such as uterine rupture, placenta accreta, and post-operative morbidity. Women undergoing five or more CS face elevated risks, necessitating tailored management strategies to mitigate both immediate and long-term health impacts. This study explores the morbidity and outcomes associated with multiple cesarean deliveries to improve patient care.Patients and Methods: This retrospective cohort study was conducted at Gurrayat General Hospital and MCH Center Arar, a tertiary care facility specializing in obstetrics and gynecology. The study included 75 women with a history of five or more cesarean deliveries. Data were collected from medical records, including patient demographics, cesarean section details, and post-operative outcomes. Statistical analyses were performed using chi-square tests and t-tests, with significance set at p < 0.05.Results: The average age of participants was 35.2 years, with a mean BMI of 31.5 kg/m². Major surgical complications occurred in 34% of cases, including uterine rupture (8%) and placenta accreta spectrum disorders (6.7%). Post-operative hemorrhage occurred in 16% of patients, and infections were documented in 12%. Long-term complications included chronic pain (20%), infertility (10.7%), and psychological effects (16%). A significant association was found between higher BMI and post-operative morbidity (p < 0.01).Conclusion: This study highlights the increased risks and complications associated with undergoing five or more cesarean sections, including major surgical issues, post-operative morbidity, and long-term health effects. These findings emphasize the need for improved management strategies and support for women with multiple cesarean histories.
Keywords: Cesarean section, morbidity, uterine rupture, placenta accreta, surgical complications, maternal health